2007
DOI: 10.1542/peds.2006-1494
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Prospective Study of Childhood Herpes Simplex Encephalitis: Is There a Broader Spectrum of Disease?

Abstract: Herpes simplex encephalitis continues to be associated with poor long-term neurologic outcomes despite appropriate therapy. Cerebrospinal fluid polymerase chain reaction results may be negative early in the course of herpes simplex encephalitis; therefore, repeat cerebrospinal fluid analysis should be considered if herpes simplex encephalitis is suspected. Atypical forms of herpes simplex virus central nervous system disease may occur in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 32 publications
11
104
1
4
Order By: Relevance
“…Even with broad testing for HSV (84% of patients), HSV encephalitis was diagnosed in only 5%, confirming recent reports that HSV encephalitis is less common in children than adults with encephalitis. 4,29,30 Despite early acyclovir therapy (not described), the outcomes after HSV encephalitis were poor, as described in recent pediatric cohorts. 30,31 Interestingly, 1 patient with HSV encephalitis relapsed with chorea and had NMDAR and D2R antibodies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even with broad testing for HSV (84% of patients), HSV encephalitis was diagnosed in only 5%, confirming recent reports that HSV encephalitis is less common in children than adults with encephalitis. 4,29,30 Despite early acyclovir therapy (not described), the outcomes after HSV encephalitis were poor, as described in recent pediatric cohorts. 30,31 Interestingly, 1 patient with HSV encephalitis relapsed with chorea and had NMDAR and D2R antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…4,29,30 Despite early acyclovir therapy (not described), the outcomes after HSV encephalitis were poor, as described in recent pediatric cohorts. 30,31 Interestingly, 1 patient with HSV encephalitis relapsed with chorea and had NMDAR and D2R antibodies. 32 The emerging theme of postviral autoimmunity is increasingly recognized, and it emphasizes the importance of considering immunotherapies in post-HSV relapses.…”
Section: Discussionmentioning
confidence: 97%
“…Although standard treatment for viral encephalitis involves acyclovir, an inhibitor of DNA polymerase (Whitley et al, 1986), poor long-term neurologic and cognitive outcomes still occur (Elbers et al, 2007;Hokkanen et al, 1996;Lahat et al, 1999). However, some have reported that although acyclovir can reduce CNS viral titres to undetectable levels, inflammatory markers remain unaffected (Lund-berg et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…PCR for HSV-1 and HSV-2, which has supplanted viral cultures and other studies as the test of choice, should be obtained from the CSF and has high sensitivity (96 %) and specificity (99 %) [67,68]. False-negative PCR can occur early in the illness [98][99][100], and if the clinical suspicion is high, aciclovir should be continued empirically and repeat CSF HSV PCR obtained within 3-7 days [43].…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…3) Falsenegative PCR studies. HSV-1 PCR may yield a false-negative, particularly early in the course of the HSVE and among children [98][99][100]. When suspicion is high, patients should be treated empirically, despite a negative PCR, and HSV PCR from the CSF should be repeated within 3-7 days [43].…”
Section: Diagnostic Pitfallsmentioning
confidence: 99%